Transformational Leadership: Principals’ Inspirational Motivation in Fostering Teachers’ Professionalism - Sholeh, Makherus; Aziz, Abd; Kholis, Nur; Gürhan, Ethem (Institut Agama Islam Negeri Imam Bonjol Padang, 2026)
Principals’ leadership plays a pivotal role in strengthening teacher professionalism, particularly in Islamic primary schools facing growing demands for quality and adaptability. This study examines how inspirational motivation, a core dimension of transformational leadership, is enacted in daily leadership practices to enhance teacher professionalism. Using a qualitative multicast design, the research was conducted in two Islamic primary schools in Indonesia. Data were gathered through in-depth interviews, participant observation, and document analysis involving 20 participants, including principals, teachers, and key stakeholders. The findings indicate that inspirational motivation is not expressed through isolated motivational speeches but through integrated and sustained leadership practices. Principals demonstrate inspirational motivation through three interconnected strategies: exemplary leadership that builds moral credibility and professional role modelling; consistent oral and written motivational communication that strengthens teachers’ professional awareness; and structured programs that institutionalize ongoing professional development. These combined practices nurture internal commitment, responsibility, and continuous competence improvement among teachers. This study proposes a contextual framework of inspirational motivation that emphasizes the interdependence of leader behaviour, symbolic communication, and organizational support. It contributes to transformational leadership literature by conceptualizing inspirational motivation as an enacted, practice-based process within Islamic primary education settings.